Fr. Remigiusz Kossakowski’s Reports about His Efforts to Achieve Election of Fr. Marcin Poczobut-Odlanicki as a Member of the French Royal Academy of Sciences (Based on His Correspondence with Poczobut) - Jakubėnas, Regina (Senoji Lietuvos literatūra, 2021)
This article concerns the activities of the ex-Jesuit Remigiusz Kossakowski (1730–1780) in the light of his correspondence, mainly in 1778, with Marcin Poczobut-Odlanicki (1728–1810), the administrator of the Vilnius Astronomical Observatory and a professor at Vilnius Academy. Kossakowski conducted a series of procedures aimed at electing Poczobut to the Academy’s corresponding members in the environment of Parisian scholars, members of the French Royal Academy of Sciences (membre correspondent de l’Académie des Sciences). He described his actions and the situation before the election in great detail in his letters to Poczobut. Not only did Kossakowski report on his efforts, but he also published numerous comments and reflections on the scientific community in Paris of that time, on the publications published in France, and their authors. Kossakowski’s correspondence with Poczobut also sheds light on his merits in promoting Poczobut’s scientific achievements in the academic community and in the activities of Vilnius Astronomical Observatory. Among other things, Kossakowski prepared a ‘memorial’ on Poczobut’s astronomical observations and disseminated it among the academicians; he welcomed scholars with a sumptuous dinner, visited academicians before the election, and presented the results of studies conducted by Poczobut. In August 1778, he contributed to the publication of an article about the royal constellation Taurus Poniatovii in the French journal Journal des Sçavants. Kossakowski’s correspondence contains many observations and reflections on Parisian customs, as well as criticism of the outstanding writers of the era, such as Voltaire and Jean-Jacques Rousseau. It also testifies to the exchange of scientific ideas between Vilnius and Paris in the era of the Enlightenment, the fact that the academic community of Vilnius had a lively contact with the French scientific community. In addition, Kossakowski’s letters reveal the author not only as an active participant in the activities for the benefit of the Vilnius Observatory and its administrator but also as a talented narrator with an outstanding rhetorical talent.
Keywords: Fr. Remigiusz Kossakowski; Fr. Marcin Poczobut-Odlanicki; French Royal Academy of Sciences (Académie des sciences); letters from Paris; the Vilnius University Astronomical observatory